Factors affecting the productivity and technical efficiency of corn farmers in Wao, Lanao del Sur and Kadingilan, Bukidnon - Pasquin, Dianarah Kristelle G.
Corn is the second most important crop in the Philippines. It is a vital part in the country's economy since it is the major source of income for one-third of Filipino farmers and 60% of its total yield is used for the production of feeds for poultry and livestock. It is an input intensive crop that it requires large amount of capital making farmers borrow money from financiers. Thus, to help farmers increase their yield without necessarily increasing their inputs' cost, and to determine the effects of financiers to the farmers' production and technical efficiency, this study was conducted. The GNU Regression Econometrics and Time-Series Library (GRETL) software and Data Envelopment Analysis Program (DEAP) were used to address the objectives of the study. Based from the Production Function model, only the factors fertilizer cost, distance and location were significant at 5% level of significance. All of the variables have negative effects except fertilizer and pesticide costs. Results also construed that farmers in Wao are more productive by 0.23% compared to farmers in Kadingilan. Moreover, it was seen that farmers with financiers are more productive by 0.125% compared to non-financed farmers. However, in the result of DEAP, non-financed farmers were more technically efficient.